2011
DOI: 10.1111/j.1756-185x.2011.01615.x
|View full text |Cite
|
Sign up to set email alerts
|

Osteoarthritis of the knees in the COPCORD world

Abstract: This paper examines and summarizes data on knee osteoarthritis (AO) in Community Oriented Program For Control Of Rheumatic Disorders (COPCORD) publications. A literature search was made through PubMed, Google, Proceedings of Asia-Pacific League of Associations for Rheumatology (APLAR) congresses, and Abstracts from APLAR congresses. Data were compiled to examine the prevalence of knee OA and knee pain, sex ratio, urban/rural differences and other risk factors. Data on knee pain and OA were available in a total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
76
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(86 citation statements)
references
References 22 publications
7
76
0
3
Order By: Relevance
“…It has been reported that in Iran, the prevalence of this complication has been higher than other studied countries (13). In both industrialized and developing countries, osteoarthritis has been increasingly and con-sidered as an important cause of pain and disability, and because of certain habits and more pressure on the knee joint, osteoarthritis of the knee is common and appears at an earlier age in Iran (14).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that in Iran, the prevalence of this complication has been higher than other studied countries (13). In both industrialized and developing countries, osteoarthritis has been increasingly and con-sidered as an important cause of pain and disability, and because of certain habits and more pressure on the knee joint, osteoarthritis of the knee is common and appears at an earlier age in Iran (14).…”
Section: Introductionmentioning
confidence: 99%
“…It is estimated to affect approximately 15% of the world population (2). In Iran 15.3% of urban and 19.3% of rural people have knee OA (3). OA is a heterogeneous and multifactorial disease and numerous pathological mechanisms have been associated in its progress.…”
Section: Introductionmentioning
confidence: 99%
“…25 This repair may be due to the change of the effect of transforming growth factor (TGF)b on local MSCs and chondrocyte, switching the Smad1/5/8 phosphorylation (due to the presence of A Disintegrin And Metalloproteinase with Thrombospondin Motifs [AD-AMTS5], probably because of synovial inflammation) to Smad2/3 phosphorylation which is a protector of joint normal cartilage. 2,[30][31][32] Why after several months this action may be reversed and the process of cartilage degradation starting again is not known. Perhaps, after a while, the transplanted MSCs loses their characteristics and become like the original resident MSCs with chaotic function.…”
Section: Discussionmentioning
confidence: 99%
“…It has a high prevalence in Asian countries (from 4.1% to 11.3%), 1 especially in Iran (from 16% to 21%). [2][3][4][5][6] Unfortunately, the available treatments are more symptomatic than preventive. Although some of them may slow down the process, there is no hope for a reversal, leading gradually to more cartilage loss and finally to joint replacement.…”
Section: Introductionmentioning
confidence: 99%